UV laser photofabrication of waveguide couplers using self-patterning organic-inorganic hybrids - Xavier, Lionnel R.; Fernandes, Vasco R.; Vicente, Carlos M. S.; Pecoraro, Édison [UNESP]; Carlos, Luis D.; Ferreira, Rute A. S.; André, Paulo S. (Wiley, 2011)
Planar waveguides with controlled refractive index were produced using thin films of sol-gel derived organic-inorganic hybrids, so called di-ureasils. Spectroscopic ellipsometry was used to characterize the films thickness and refractive index. UV-laser direct-writing method was used to produce Y-splitter structures with coupling ratio of 50% without the need of photoinitiators.
Keywords: organic-inorganic hybrids; inte grated optics; UV-laser writing; Y-splitter; passive optical networks.